Next Generation Sensors and Systems - Mukhopadhyay, Subhas Chandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Written by experts in their area of research, this book has outlined the current status of the fundamentals and analytical concepts, modelling and design issues, technical details and practical applications of different types of sensors and discussed about the trends of next generation of sensors and systems happening in the area of Sensing technology. This book will be useful as a reference book for engineers and scientist especially the post-graduate students find will this book as reference book for their research on wearable sensors, devices and technologies.  .
Graphene Based Physical and Chemical Sensors -- Design and Realization of A Planar Interdigital Microsensor for Biological Medium Characterization -- Molecularly Imprinted Impedimetric Sensing of Phthalates; a Real-Time Assay Technique.- Magnetic and Transport Properties of M-Cu (M=Co, Fe) Microwires -- Giant Magnetoimpedance Effect of Amorphous and Nanocrystalline Glass-Coated Microwires.-Aged Zirconia Electrochemical Oxygen Sensor Activation and Reactivation Using Nemca -- A New Scheme for Determination of Respiration Rate in Human Being Using Mems Based Capacitive Pressure Sensor -- Monitoring of the Lung Fluid Movement and Estimation of Lung Area Using Electrical Impedance Tomography.-Activity and Anomaly Detection In Smart Home: A Survey -- Real-Time Monitoring Of Meat Drying Process Using Electromagnetic Wave Sensors -- An Improved Fusion Algorithm for Estimating Speed from Smartphone's Ins/Gps Sensors -- Monitoring Water in Treatment and Distribution System -- An Application of the Frame Theory for Signature Extraction in the Analysis of 3d Point Clouds.
Keywords: Electronics; Signal processing; Measurement; Measuring instruments; Electronics and Microelectronics, Instrumentation; Signal, Speech and Image Processing; Measurement Science and Instrumentation